Datos del material tipo de Culicoides (Drymodesmyia) Bakeri Vargas (Dipteria: Ceratopogonidae) - Huerta, Herón (Instituto de Ecología, A.C., 2007)
The adult male and female of Culicoides bakeri Vargas are redescribed based on re-examination of the type material and examination of other specimens from the type locatity, deposited in the Collection of Arthropods of Medical Importance (CAIM).